Ocular heat exchange indices in terminal neovascular glaucoma patients with proliferative diabetic retinopathy - Zadorozhnyy, O. S.; Guzun, O.V.; Kustrin, T. B.; Korol, A. R.; Naumenko, V.A.; Pasyechnikova, N. V. (Ukrainian Journal of Ophthalmology, 2025)
Background: The heat processes in patients with diabetes mellitus are still poorly understood. Purpose: To examine temperature of and heat flow (HF) density from the ocular surface in the eyes of patients with neovascular glaucoma that had developed in the presence of proliferative diabetic retinopathy (PDR). Material and Methods: In this open pilot study, 25 patients (50 eyes) with PDR in both eyes were under observation. In each patient, one eye was diagnosed with terminal neovascular glaucoma, and received laser treatment that included three sessions of transscleral contact-compression laser cyclocoagulation (TSCC LC). Before and 1 month after laser treatment, patients underwent examinations in both eyes as follows: best-corrected visual acuity testing, intraocular pressure (IOP) measurements, and measurements of temperature of the external corneal surface and HF density from the eye. Results: Before laser treatment, mean corneal surface temperature and mean HF density from the eye in glaucomatous eyes were 33.9 ± 0.9°С and 5.8 ± 1.6 mW/cm2, respectively, and were lower than in the fellow eyes (34.4 ± 1.0°С (p = 0.08) and 6.9 ± 1.4 mW/cm2 (p = 0.02), respectively). At 1 month after laser treatment, in glaucomatous eyes, mean IOP decreased from 36.3±5.4 mmHg to 25.8±4.6 mmHg (p =0.000), mean corneal surface temperature increased to 34.5 ± 0.9°С (p = 0.06), and mean HF density from the eye increased to 8.3±1.99 mW/cm2 (p =0.000). Conclusion: In patients with terminal neovascular glaucoma in one eye only, there was an asymmetry in ocular heat exchange indices between glaucomatous eyes and fellow eyes (with normal IOP). In addition, an increase in HF density from the eye in the presence of decreased IOP in eyes with terminal neovascular glaucoma after transscleral contact-compression laser cyclocoagulation seems to result from an increased intraocular thermal gradient in the presence of improved ocular hemodynamics.